2011
DOI: 10.5897/ajpp10.302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspartame on some oxidative stress parameters in liver and kidney of rats

Abstract: Aspartame is one of the most widely used artificial sweeteners in over 90 countries worldwide. It is a highly intensity sweetener added to a large variety of food, most commonly found in low calorie beverages, desserts and table top sweeteners added to tea or coffee. The present study examined whether the daily oral administration of ASP (40 mg/kg) for 2, 4 and 6 weeks induce oxidative stress in the liver and kidney of male albino rats. Lipid peroxidation (LPO), glutathione reduced (GSH) levels as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…This opinion is in agreement with our study which observed a significant elevation in lipid peroxidase level in the liver tissue of rats after 28 days treatment with aspartame. A similar result was reported by [28]. Lipid peroxidation induce oxidative damage to proteins and nucleic acids which lead to increased collagen and ground substance formation [42].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This opinion is in agreement with our study which observed a significant elevation in lipid peroxidase level in the liver tissue of rats after 28 days treatment with aspartame. A similar result was reported by [28]. Lipid peroxidation induce oxidative damage to proteins and nucleic acids which lead to increased collagen and ground substance formation [42].…”
Section: Discussionsupporting
confidence: 71%
“…Free radicals affect Na/K pump function leading to Na accumulation and water migration to the cells [26]. Moreover, methanol could increase lipid peroxidation which increase the surface charge density and act as an auto catalytic mechanism leading to oxidative destruction of cellular membrane as noted by other reports [27,28].…”
Section: Discussionmentioning
confidence: 94%
“…Recently from previous studies on aspartame and its metabolite, altering the oxidative status of the cells was investigated. Oral aspartame (75 mg/kg body weight/day) consumption causes oxidative stress in brain 21 and its (40 mg/kg bw/day) consumption caused oxidative stress in brain, 22 liver and kidney, 23 and also in immune organs. 24 This inadequacy, combined with the general limited knowledge about the safety/potential toxigenic effects of substances widely present in the industrialized diet, motivated the design of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of Glucose homeostasis by aspartame ingestion was also well documented a decade before [25]. Aspartame had the capacity to alter the normal antioxidant enzyme pool in many organs like liver and kidney [30]. Even longterm consumption of aspartame could lead to oxidative stress in the erythrocytes and blood cells too [31].…”
Section: Possible Associated Health Concernsmentioning
confidence: 99%